Distances between mandibular posterior teeth and the WALA ridge in Peruvians with normal occlusion - Carla Y. Kong-Zárate; Marcos J. Carruitero; Will A. Andrews
ABSTRACT Objective: The purposes of this investigation were to determine the horizontal distances between the mandibular posterior teeth and the WALA ridge in a sample of Peruvians with normal occlusion and to compare them by tooth type, sex, arch side, and age groups. Methods: 65 dental casts of subjects with normal occlusion were collected. Posterior teeth, except for third molars, were evaluated. The horizontal distances between the occluso-gingival midpoints of the buccal surfaces (FA points) of each tooth and the WALA ridge were measured using a modified digital caliper. The values between each different tooth type within the sample were compared using the ANOVA and Scheffe tests, while comparisons by sex, arch side and age groups, using the Student's t-test. Results: The mean distances in the sample was 0.96 mm for first premolars, 1.45 mm for second premolars, 2.12 mm for first molars and 2.55 mm for second molars. Statistically significant differences between each of the four tooth types were found. There were no significant differences found between sex, arch side and age groups. Conclusion: The horizontal distances between the mandibular posterior teeth and the WALA ridge increased progressively from the first premolars to the second molars in Peruvians with normal occlusion. The WALA ridge was a good landmark to evaluate the positions of posterior teeth in Peruvians with normal occlusion.